Is breakfast the most important meal of the day?. Issue 4 (13th June 2016) - Betts, James A.; Chowdhury, Enhad A.; Gonzalez, Javier T.; Richardson, Judith D.; Tsintzas, Kostas; Thompson, Dylan
Abstract : The Bath Breakfast Project is a series of randomised controlled trials exploring the effects of extended morning fasting on energy balance and health. These trials were categorically not designed to answer whether or not breakfast is the most important meal of the day. However, this review will philosophise about the meaning of that question and about what questions we should be asking to better understand the effects of breakfast, before summarising how individual components of energy balance and health respond to breakfast v. fasting in lean and obese adults. Current evidence does not support a clear effect of regularly consuming or skipping breakfast on body mass/composition, metabolic rate or diet-induced thermogenesis. Findings regarding energy intake are variable, although the balance of evidence indicates some degree of compensatory feeding later in the day such that overall energy intake is either unaffected or slightly lower when breakfast is omitted from the diet. However, even if net energy intake is reduced, extended morning fasting may not result in expected weight loss due to compensatory adjustments in physical activity thermogenesis. Specifically, we report that both lean and obese adults expended less energy during the morning when remaining in the fasted state than when consuming a prescribed breakfast. Further research is required to examine whether particular health markers may be responsive to breakfast-induced responses of individual components of energy balance irrespective of their net effect on energy balance and therefore body mass.